Giant Desmoid Tumor of the Anterior Abdominal Wall in a Young Female: A Case Report. (21st April 2013) - Koshariya, Mahim; Shukla, Samir; Khan, Zuber; Vikas, Vaibhav; Pratap Singh, Avinash; Baghel, Puspendra; Pendro, Varun; Kirti Jain, Vishal; Jagdish Jai, Shrikant; Kumar, Sanjeev; Songra, M. C.
Abstract : Desmoid tumors (also called desmoids fibromatosis) are rare slow growing benign and musculoaponeurotic tumors. Although these tumors have a propensity to invade surrounding tissues, they are not malignant. These tumors are associated with women of fertile age, especially during and after pregnancy. We report a young female patient with a giant desmoid tumor of the anterior abdominal wall who underwent primary resection. The patient had no history of an earlier abdominal surgery. Preoperative evaluation included abdominal ultrasound, computed tomography, and magnetic resonance imaging. The histology revealed a desmoid tumor. Primary surgical resection with immediate reconstruction of abdominal defect is the best management of this rarity. To the best of our knowledge and PubMed search, this is the first case ever reported in the medical literature of such a giant desmoid tumor arising from anterior abdominal wall weighing 6.5 kg treated surgically with successful outcome.